Pediatric Round Pneumonia - Yen-Lin Liu; Ping-Sheng Wu; Li-Ping Tsai; Wen-Hsin Tsai (Pediatrics and Neonatology, 2014)
“Round pneumonia” or “spherical pneumonia” is a well-characterized clinical entity that seems to be less addressed by pediatricians in Taiwan. We herein report the case of a 7-year-old boy who presented with prolonged fever, cough, and chest X-rays showing a well-demarcated round mass measuring 5.9 × 5.6 × 4.3 cm in the left lower lung field, findings which were typical for round pneumonia. The urinary pneumococcal antigen test was positive, and serum anti-Mycoplasma pneumoniae antibody titer measurement using a microparticle agglutination method was 1:160 (+). After oral administration of antibiotics including azithromycin and amoxicillin/clavulanate, which was subsequently replaced by ceftibuten due to moderate diarrhea, the fever subsided 2 days later and the round patch had completely resolved on the 18th day after the diagnosis. Recent evidence suggests treating classical round pneumonia with antibiotics first and waiving unwarranted advanced imaging studies, while alternative etiologies such as abscesses, tuberculosis, nonbacterial infections, congenital malformations, or neoplasms should still be considered in patients with atypical features or poor treatment response.